Controlling Fiscal Corruption - Chand, Sheetal (IMF Working Papers; Working Paper, 1997)
This paper examines the issue of controlling fiscal corruption by providing incentives to fiscal officers. First, a case study of a successful attack on corruption is presented that shows the importance of attending to the conditions of service of fiscal officers. Second, a model is developed drawing on the conclusions of the case study that shows their consistency with optimization behavior. It confirms that simply providing bonuses is not enough. Corruption at higher levels of management has to be contained so as to allow bonuses to become more effective, and thereby to initiate a virtuous circle.